PENGARUH KONFLIK PERAN GANDA, STRES KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN WANITA - Suci Saraswati, Kadek Ayu; Putu Indian, Ni Luh (Ekonis: Jurnal Ekonomi dan Bisnis, 2023)
In the world of employment, not only men have the opportunity to occupy important positions in the organization, women also have the same opportunities. One company with a male-dominated workforce such as a consumer finance company also provides equal opportunities for female workers. The object of this research is PT. Federal International Finance Denpasar-2 Branch due to the decline in the performance of female employees which is thought to be influenced by several causes including multiple role conflicts, work stress, and work discipline. This study aims to determine the effect of dual role conflict, work stress and work discipline on the performance of female employees. The population of this study were married female employees with a sample of 30 respondents. The data analysis technique uses Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, F Test and t Test. The results of the study found: (1) dual role conflict had a significant negative effect on the performance of female employees, (2) work stress had a significant negative effect on the performance of female employees, (3) work discipline had a significant positive effect on the performance of female employees. To improve the performance of female employees, the company is expected to be able to provide encouragement or encouragement to employees, always escort employees at work, give warnings or punishments to employees who do not obey the rules and always help employees when experiencing difficulties at work.Keywords: Multiple Role Conflict, Work Stress, Work Discipline and Employee Performance